SAT-034 The Effect of Natesto on Spermatogenesis, Reproductive Hormones, and Hypogonadal Symptoms. A Phase IV Study - Masterson, Thomas A (J Endocr Soc, 2020)
INTRODUCTION AND OBJECTIVE: Exogenous testosterone (T) therapy is typically long-acting and causes azoospermia in up to 65% of the men. Natesto, dosed three times a day, is a short-acting, FDA approved nasal testosterone available since 2015. We hypothesized that Natesto can preserve spermatogenesis due to its short-acting property. METHODS: We prospectively enrolled hypogonadal men aged 18-55 years with two serum T levels < 300 ng/dL (drawn before 10 AM), symptoms, and 2 semen analyses (SA) with total motile sperm counts (TMSC) > 5 million in a phase IV clinical trial. Eligible men received Natesto for 6 months. Serum T, luteinizing hormone (LH), follicle stimulating hormone (FSH), 17-hydroxyprogesterone (17-OHP), 2 SA, and testis volume were collected at baseline and after 3 and 6 months of therapy. Symptoms were evaluated using the international index of erectile function 6 (IIEF-6) and the short form 36 (SF-36) questionnaires. The primary endpoints were change in T, LH, FSH, sperm concentration, sperm motility, and TMSC. Secondary end points were change in symptoms, testis volume, and adverse events (AEs). Data are presented as means (SD), t-test was used to compare changes after 3 and 6 months, p<0.05 was considered significant. RESULTS: In total, 102 men were screened, and 60 men (age 19-55 years) enrolled. Of the 60 men, 44 completed 3 months, 33 completed 6 months, and 17 dropped out. Mean serum T increased from hypogonadal at baseline to 3 and 6 months (p=0.005), LH and FSH decreased (p=0.03) but remained within the normal range (2-5 IU/mL). Most importantly, semen parameters remained unchanged after 3 and 6 months of T therapy. Only 3 (7.5%) men had severe oligospermia and one (2.5%) became azoospermic but recovered at 6 months after discontinuation. Testis volume and intratesticular T (serum 17-OHP) were maintained at 3 and 6 months. There was improvement across all sub-domains of the IIEF as well as improvement in questions related to energy in the SF-36. A total of 10 men dropped out due to nasal irritation. CONCLUSIONS: This phase IV clinical trial demonstrated that Natesto increased serum T, improved hypogonadal symptoms, maintained gonadotropins, testis volume, intratesticular testosterone and semen parameters. Natesto, and other short acting forms of testosterone therapy may help hypogonadal men maintain fertility.